Penerimaan Masyarakat Terhadap Penguatkuasaan Agensi Antidadah Kebangsaan Malaysia - Azmawaty Mohamad Nor; Farhana Nabila Fakaruddin; Shanina Sharatol Ahmad Shah; Haslee Sharil Lim Abdullah; Mohd Awang Idris; Zolkifli Mohd Dom (Agensi Anti Dadah Kebangsaan (AADK), 2024)
Non-Indexed Publication